2020
DOI: 10.35940/ijmh.k1053.0741120
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors of Zakat Compliance Behavior of Muzakki: Evidence from Malaysia

Abstract: This study is to examine the variables and determining factors of zakat compliance behavior of muzakki in Malaysia. This study explores 24 determining variables of zakat compliance behavior based on Islamic concept and also previous studies. 285 muzakki were being respondents at 14 states in Malaysia. Data was analyzed by factor analysis with varimax rotation using SPSS 20. The results showed there are 20 variables and 5 groups of factors that form zakat compliance behavior of muzakki in Malaysia. The implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The results of the study conducted by (Mohd Yusoff & Hanapi, 2016) found that the availability of online payment facilities was one of the factors that could encourage muzakki to pay zakat. The results of this study are supported by (Bulutoding et al, 2020) which also found that muzakki tend to be influenced to make zakat payments if the online zakat system facilitates them in making zakat payments. However, the BAZNAS of Makassar revealed slightly different view from the results of these studies.…”
Section: Utilization Of Information Technology In Ziswaf Fundraisingsupporting
confidence: 74%
“…The results of the study conducted by (Mohd Yusoff & Hanapi, 2016) found that the availability of online payment facilities was one of the factors that could encourage muzakki to pay zakat. The results of this study are supported by (Bulutoding et al, 2020) which also found that muzakki tend to be influenced to make zakat payments if the online zakat system facilitates them in making zakat payments. However, the BAZNAS of Makassar revealed slightly different view from the results of these studies.…”
Section: Utilization Of Information Technology In Ziswaf Fundraisingsupporting
confidence: 74%